Компоненты мужской одежды крымских татар второй половины XIX – начала XX ст. - Аблямитова, Л.Х. (Культура народов Причерноморья, 2014)
В статье автор выявляет компоненты верхней мужской одежды крымских татар. Анализ
покроя верхней одежды крымских татар позволяет утверждать, что в зависимости от кроя спинки
они делятся на следующие виды: с приталенным станом, прямой спинкой, отрезным лифом. Различия
выявляются и в конструктивных особенностях деталей одежды – форма ворота, длина рукава, остова,
в орнаменте, цветовом решении. Тем самым автор раскрывает региональные особенности типов
верхней одежды в мужских комплексах. У статті автор виявляє компоненти верхнього чоловічого одягу кримських татар. Аналіз
покрою верхнього одягу кримських татар дозволяє стверджувати, що залежно від крою спинки, вони
поділяються на наступні види: з притуленим станом, прямою спинкою, відрізним ліфом. Відмінності
виявляються й у конструктивних особливостях деталей одягу – форма коміра, довжина рукава, остова,
в орнаменті, колірному рішенні. Тим самим автор розкриває регіональні особливості типів верхнього
одягу в чоловічих комплексах. The author identifies the components of Crimean Tatars’ men’s wear. The analysis of Crimean
Tatars’ men’s wear cut suggests that, depending on the back’s cut, they are divided into the following types:
short-cut figure, straight back, detachable bodice. Each type of men’s wear, depending on the element’s cut,
fabrication material and seasonal destination divided into the following types:
Type 1- straight silhouette divided into the following subtypes:
Subtype 1 – Jacket “Marka”;
Subtype 2 – Bathrobe “Juba”;
Subtype 3 – Sheepskin coat “Tone”;
Subtype 4 – Fur coat “Tone”;
Subtype 5 – Felt cloak “Kurk”.
Type 2 – with the whole form – fitting back divided into the following subtypes:
Subtype 1 – Sleeveless jacket “Yrka”;
Subtype 2 – Jacket “Miytan”;
Subtype 3 – Camisole “Chuppe”;
Type 3 – with detachable bodice:
Subtype 1 – Сaftan “Chekmen”.
The differences detected in the structural features of wear’s details – form of collar, sleeve’s length, frame,
ornament, colour.
The analysis of top wear with straight back on the base of cartographic materials shows that top wear in the
steppe and mountain regions had elongated shape. The climate conditions in the coastal regions permit to wear
short-cut clothes.
Thus, the author reveals regional features of top wear’s types in male set.